Kedudukan Hukum Alat Bukti dalam Tindak Pidana Pelecehan Seksual di Peradilan Pidana Indonesia - Kevin Mandala; Erdianto Erdianto; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Evidence occupies an important position. The judge in making a decision will need a lot of time tostudy and analyze in depth the existing evidence and the results of the evidence will be used as aguide in making a decision. Indonesia adheres to a system of proof according to negative law orNegative Wettelijk Stelsel, this can be seen in the provisions of Article 183 of the CriminalProcedure Code, where to convict the Defendant, the Judge must have at least two valid pieces ofevidence plus valid evidence. the judge's conviction, meaning that at least two valid pieces ofevidence, the judge obtains confidence that the crime actually occurred and the defendant was theperpetrator. Therefore, the judge must carefully, thoroughly, and maturely assess and consider thevalue of an evidence by examining the extent to which the